Aktivitas Membaca Nyaring di Sekolah Dasar - Kurniasih, Nuning; Damayani, Ninis A; Rusmana, Agus; Prijana, Prijana; Nurislaminingsih, Rizki (Universitas Pahlawan Tuanku Tambusai, 2025)
In order to build a literate generation that loves books and takes pride in Indonesia's cultural heritage, the Library and Information Science Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, is organizing a Community Service Program (PKM) themed “Reading Aloud.” One of the activities of this PKM is the delivery of material on reading aloud for teachers at SDN Lontong Jatigede Sumedang on August 6, 2025. The training session had 30 participants, including teachers from SDN Lontong, lecturers, and students from the Library and Information Science Program. The training material covered the concept, objectives, and benefits of reading aloud, as well as activities related to reading aloud in various contexts and at elementary schools, delivered through interactive lectures. At SDN Lontong, reading aloud activities have already been implemented. However, teachers need to continue providing positive encouragement and giving students ample opportunities to practice, supported by the provision of books that are appealing to students. This training is expected to enhance teachers' knowledge and skills in conducting reading aloud activities during the learning process at school.